Enhancement of direct somatic embryogenesis of Eurycoma longifolia in vitro: PGR, basal medium and other factors affecting somatic embryo formation - NADIAWATI, ALIAS (2014)
An alternative protocol for somatic embryo induction directly from cotyledon of Eurycoma longifolia (Tongkat Ali), was established in this study. Due to its high usage in medicinal traditional treatment, the demand has lead to excessive harvest through destructive method, which has caused serious shortage of the plant in the wild. Thus, somatic embryogenesis is aimed to propagate by in vitro technique. Twelve combination of plant growth regulators (PGR); 2,4-D, IBA, IAA, PIC, KIN, BAP and ZTN were added in Modified Murashige Skoog media (MMS) to induce direct growth of somatic embryogenesis. While, in order to optimize embryo growth rates, five basal media (MS, Modified MS, Y3, WPM and B5) were also evaluated. In addition, the effects of light conditions, activated charcoal (AC), sucrose concentration and medium renewal were determined for their influence on direct somatic embryogenesis. One Way Analysis of Variance (ANOVA) showed that the highest percentage of somatic embryogenesis induction was found significant when using ZTN and IBA at 7%±1.05 for the PGR treatments and MMS media supplemented with ZTN and IBA at 12.5%±0.99 as compared with the other basal media tested. The addition of sucrose higher than 30g/L was found decreased embryogenesis efficiency at a significant value (P˂0.05), and explants that were incubated in darkness (18.5% ± 0.81) has proved to increase the somatic embryo formation as compared to other factors tested. While, the addition of AC was not required for the somatic embryogenesis induction, as it reduced the rates of embryos growth. The green, globular somatic embryos were then subsequently multiplied by using temporary immersion system; RITA®. The direct somatic embryo obtained could be further used for development of plantlet regeneration system in the propagation of Eurycoma longifolia.